Implementasi Undang-Undang Nomor 21 Tahun 2019 Tentang Karantina Hewan, Ikan Dan Tumbuhan Pada Balai Besar Karantina Pertanian Belawan - Hotma Diana Siregar; Maksum Syahri Lubis; Adam Adam (Universitas Medan Area, 2021)
This study aims to analyze the implementation of plant quarantine policies in the work unit of the Belawan Agricultural Quarantine Center. This study uses a qualitative approach where the researcher is the key instrument, the data collection technique is trangulation (observation, interviews and documentation), the data obtained tends to be qualitative data, the data analysis is qualitative and the results of qualitative research are to understand the meaning and construct the phenomenon of policy implementation. plant quarantine service regulations. The results of the study indicate that the implementation of the policy on plant quarantine service regulations has not been able to be carried out optimally even though the stipulated legal regulations have been enforced. This is due to the lack of communication or dissemination of information about quarantine to the entire community, especially service users. Besides, other indicators are due to the lack of civil servant field officers at the Belawan Agricultural Quarantine Center and the lack of technology that supports services at the Belawan Agricultural Quarantine Center.